Self-evaluation of competences of the special educators and rehabilitators in the special institutions - Chichevska Jovanova, Natasha; Dimitrova Radojichikj, Daniela (My University, 2009)
The primary goal of this empirical research was to determinate how much has current education helped special educators and rehabilitators in forming separate competences, and if those competencies correspond to the desired ones, which are necessary for the work of the special educators and rehabilitators. The results have shown that one type of the competences in the program had been neglected up to now. Therefore, it is necessary for this fact to be taken into consideration when designing the new study programs.
Самоевалуација на компентенциите на дефектолозите од посебните установи
Keywords: competences, self-evaluation, special educators and rehabilitators.